2019
DOI: 10.1103/physrevb.100.064402
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions of skyrmion lattices in synthetic antiferromagnets

Abstract: Thin magnetic films with Dzyaloshinskii-Moriya interactions are known to host skyrmion crystals, which typically have a hexagonal lattice structure. We investigate skyrmion-lattice configurations in synthetic antiferromagnets, i.e., a bilayer of thin magnetic films that is coupled antiferromagnetically. By means of Monte-Carlo simulations, we find that by tuning the interlayer coupling the skyrmion lattice structure can be tuned from square to hexagonal. We give a simple interpretation for the existence of thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…1(a). The triangular skyrmion lattice can be described by the superposition of three magnetic modulation vectors q i (i = 1, 2, 3) and a uniform out-of-plane spin component [53][54][55][56][57]; see green arrows in Fig. 1(b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a). The triangular skyrmion lattice can be described by the superposition of three magnetic modulation vectors q i (i = 1, 2, 3) and a uniform out-of-plane spin component [53][54][55][56][57]; see green arrows in Fig. 1(b).…”
Section: Methodsmentioning
confidence: 99%
“…It may affect the static lattice structure as well as the lattice dynamics of skyrmions. The static lattice structure of a skyrmion solid may be manipulated by an external force or field acting on all skyrmions [52][53][54][55][56][57]. For example, Karube et al have demonstrated that the transition between a triangular skyrmion lattice and a square skyrmion lattice by varying the temperature and magnetic field [53].…”
Section: Introductionmentioning
confidence: 99%